2000
DOI: 10.1590/s1415-43662000000200005
|View full text |Cite
|
Sign up to set email alerts
|

Estresse salino em plântulas de milho: parte I análise do crescimento

Abstract: RESUMOO trabalho foi conduzido em casa de vegetação, objetivando-se avaliar o efeito do estresse salino sobre o crescimento de cultivares de milho com tolerância diferenciada à salinidade. Foi utilizado um arranjo fatorial 2 x 5 com duas cultivares de milho (P-3051 e BR-5011) e cinco níveis de cloreto de sódio na solução nutritiva (0, 25, 50, 75 e 100 mol m -3). Avaliaram-se a matéria seca (MS) da parte aérea e raízes, razão parte aérea/raiz, área foliar (AF), taxas de crescimento absoluto (TCA), relativo (TCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
8

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 22 publications
1
2
0
8
Order By: Relevance
“…This result indicates that the effect of salinity was more pronounced in the shoot than in the root, suggesting that this organ is more tolerant to salt stress. Similar results were obtained by Azevedo Neto & Tabosa (2000), with maize plants under salt stress. These authors reported that the roots seem to better withstand salinity than the shoots, a phenomenon that could be associated with faster osmotic adjustment and slower loss of turgor in the roots, if compared to the shoots, in addition to providing a better protection against oxidative stress (Abreu et al 2008).…”
Section: Resultssupporting
confidence: 87%
“…This result indicates that the effect of salinity was more pronounced in the shoot than in the root, suggesting that this organ is more tolerant to salt stress. Similar results were obtained by Azevedo Neto & Tabosa (2000), with maize plants under salt stress. These authors reported that the roots seem to better withstand salinity than the shoots, a phenomenon that could be associated with faster osmotic adjustment and slower loss of turgor in the roots, if compared to the shoots, in addition to providing a better protection against oxidative stress (Abreu et al 2008).…”
Section: Resultssupporting
confidence: 87%
“…Competition between potassium and sodium under salt stress severely reduces potassium content in both leaves and roots of maize (Alberico and Cramer 1993;de Azevedo Neto and Tabosa 2000;Kaya et al 2010) and reduces potassium content by up to 64 % in the symplast of expanding tissues under salt stress (Shahzad et al 2012). Moreover, salt stress not only reduces potassium uptake rates but, to a greater extent, disturbs potassium translocation from root to shoot tissues in maize leading to lower potassium shoot contents than root contents (Shahzad et al 2012).…”
Section: Mineral Uptake and Assimilationmentioning
confidence: 99%
“…Resultados similares foram obtidos por AZEVEDO NETO & TABOSA (2000), que verificaram maior sensibilidade à salinidade no crescimento da parte aérea de plantas de milho, enquanto as raízes mantiveram seu desenvolvimento.…”
Section: Resultsunclassified
“…Assim, o comportamento de diferentes espécies agrícolas, como soja (SANTOS et al, 1996;CATUCHI et al, 2011), arroz (ROSHANDEL, 2007 e milho (AZEVEDO NETO & TABOSA, 2000;CONUS et al, 2009), tem sido objeto de estudo em diferentes condições de estresses ambientais, com destaque para o estresse salino e hídrico, visto que esses ambientes são cada vez mais frequentes na agricultura.…”
Section: Introductionunclassified